Innovative scripts and spellings in Roman Egypt: investigations into script conventions, domains, shift, and obsolescence as evidenced by hieroglyphic, hieratic, demotic, and Old Coptic manuscripts - Love, EOD (2019)
Innovative Scripts and Spellings in Roman Egypt studies the hieroglyphic, hieratic, Demotic/demotic, and Old Coptic manuscripts which evidence the conventions governing script use, the domains of writing those scripts inhabited, and the shift of scripts and their domains, before the obsolescence of Egyptian writing during the Roman Period. Utilising macro-level frameworks from sociolinguistics, the textual culture from four case study sites of the 1st and 2nd centuries CE are contextualised within the communities of speech, script, and practice constituting the priesthoods that produced them. Utilising micro-level frameworks from linguistics, both the scripts of the Egyptian writing system written, and the way the orthographic methods fundamental to those scripts changed, are typologised. Additionally, this study treats the way in which logographic vs alphabetic orthographies are deciphered and understood by the reading brain, and the rationales behind (ortho)graphic shift, such as where conventional as opposed to innovative spellings sit along continua of orthographic depth. By analogy to language death in speech communities, current scholarship on script obsolescence in Mesoamerica, Mesopotamia, and Egypt is appraised, and by problematising generalised synoptic narratives of obsolescence, the phenomenon of domain-by-domain language and script shift is then compared directly to that of domain-by-domain obsolescence of the scripts of the Egyptian writing system. “Innovative scripts and spellings” are analysed at Oxyrhynchus, Tebtunis, Soknopaiou Nesos, and Narmouthis, and a synthesis of the evidence these provide for script conventions, domains, shift, and obsolescence is undertaken. In doing so, this study draws conclusions on how the unprecedented pressures on priestly populations during the 2nd century CE are evidenced in, and a cause of, the (ortho)graphic innovations attested, and how this informs upon the domain-by-domain shift in conventions and scripts, and eventual tip of hieratic towards obsolescence during the 2nd century CE.